THE IMPACT OF THE SHOW-AND-TELL METHOD BY SCHOOL COUNSELORS IN INCREASING STUDENTS' SELF-CONFIDENCE IN THE CLASSROOM - Hengki Yandri; Farid Imam Kholidin; Lilis Lismayaningsih; Dosi Juliawati (LP4MK STKIP PGRI Lubuklinggau, 2022)
Abstract: Self-confidence is essential for students in the classroom learning process, so school counselors must increase student confidence. One of the methods used by school counselors is the show-and-tell method. So the purpose of this study is to uncover the effects of the show-and-tell method in increasing student confidence in the classroom. This research is a type of qualitative research with descriptive analysis. Then for the collection of informants, a snowball sampling technique is used with key informants of school counselors at The State Junior High School 4 Sungaipenuh City. The data is revealed using a structured interview format, and then the interview data is processed through the data reduction stage, data presentation, and conclusion drawing; so on to maintain the validity of the data is carried out by triangulation of the data. The results of this study revealed that the show-and-tell method carried out by school counselors on students can make students become confident individuals in the classroom.